Design informatics navigating dynamic knowledge flows in discontinuous innovation enterprises - Ibrahim, Rahinah (Universiti Putra Malaysia Press, 2013)
This paper presents the emergence of design informatics where the fields of business management and computer science merge to support profitable sustainable innovation processes. The paper chronicles the journey to find solutions to mitigate costly knowledge losses during complex product innovation processes, the recent successes and the future of this emerging field by the Environmental Design Integration Research Group at the Faculty of Design and Architecture, Universiti Putra Malaysia. The paper describes knowledge loss as the inability of continuous progressive flow of any necessary working knowledge for completing a task during a product’s innovation lifecycle process. These knowledge losses keep recurring thus causing unnecessary delays and costing significant losses to their respective enterprises. The author’s doctoral dissertation found the problematic sources in four operating environmental characteristics for such complex enterprises—1) having multiple sequential and concurrent workflows, 2) having discontinuous memberships in the organization overseeing each different workflow, 3) having multiple interdependent tasks between multiple workflows, and 4) having tacit regression in their working knowledge-dominant areas. Founded on these four characteristics, the author has advanced design research investigations into understanding the product development processes for successful IT/ICT integration and understanding stakeholders’ behaviour and cognition for successful collaborations. Furthermore, her investigations have expanded to understand and streamline people and processes that utilize different knowledge types and sustainable resources for successful product innovations. With reference to completed dissertations she had supervised, the author discusses the types of knowledge contributions, the dominant research methodologies conducted, and the trans-disciplinary supervisory involved. The paper concludes with explanation how these findings become the foundation for the field of Design Informatics at Universiti Putra Malaysia. The paper recommends on how the new field can support the Economic Transformation Programme for Malaysia in the future.